Patient‐specific assessment of dysmorphism of the femoral head–neck junction: a statistical shape model approach. Issue 4 (8th January 2016) - Khanduja, Vikas; Baelde, Nick; Dobbelaere, Andreas; Van Houcke, Jan; Li, Hao; Pattyn, Christophe; Audenaert, Emmanuel A.
Abstract: Background: Objective quantification of anatomical variations about the femur head–neck junction in pre‐operative planning for surgical intervention in femoro‐acetabular impingement is problematic, as no clear definition of average normal anatomy for a specific subject exists. Methods: We have defined the normal‐equivalent of a subject's anatomy by using a statistical shape model and geometric shape optimization for finding correspondences, while excluding the femoral head–neck junction during the fitting procedure. The presented technique was evaluated on a cohort of 20 patients. Results: Difference in α ‐angle measurement between the actual morphology and the predicted normal‐equivalent, averaged 1.3° (SD 1.7°) in the control group versus 8° (SD 7.3°) in the patient group (p < 0.05). Conclusions: Defining normal equivalent anatomy is effective in quantifying anatomical dysmorphism of the femoral head–neck junction and as such can improve presurgical analysis of patients diagnosed with femoro‐acetabular impingement. Copyright © 2016 John Wiley & Sons, Ltd.